Tinjauan Hukum Ketenagakerjaan terhadap Peran Strategis Peraturan Perusahaan dalam Menjaga Keseimbangan Hubungan Industrial Antara Pengusaha dan Pekerja - Siti Izzati; Sanusi Sanusi; Soesi Idayanti (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2026)
Industrial relations are one of the main pillars in national employment development because they are directly related to company productivity, worker protection, and business continuity. In practice, employment relations are often colored by various disputes arising from unclear regulations regarding the rights and obligations of the parties. Company Regulations (PP) are present as a legal instrument that functions to regulate work conditions, company rules and regulations, the rights and obligations of workers and employers so as to create legal certainty in employment relations. This study aims to analyze the strategic role of Company Regulations in maintaining the balance of industrial relations based on the perspective of Indonesian labor law and identify various factors that influence the effectiveness of their implementation. The study uses a normative legal research method with a statutory approach, a conceptual approach, and a case approach. The analysis was conducted on various provisions of labor law, expert doctrines, and the development of industrial relations policies in Indonesia. The results of the study indicate that Company Regulations have a strategic position as a preventive instrument in creating legal certainty, protecting the rights and obligations of the parties, improving work discipline, strengthening corporate governance, and preventing industrial relations disputes. The effectiveness of Company Regulations is greatly influenced by their compliance with laws and regulations, employee participation in their development, transparency of their substance, and consistent implementation by company management. Therefore, the development of Company Regulations must prioritize the principles of justice, balance, legal certainty, and good faith to achieve harmonious, dynamic, and equitable industrial relations.